Fossil herbivore stable isotopes reveal middle Pleistocene hominin palaeoenvironment in 'Green Arabia'. Issue 12 (December 2018) - Roberts, Patrick; Stewart, Mathew; Alagaili, Abdulaziz; Breeze, Paul; Candy, Ian; Drake, Nick; Groucutt, Huw; Scerri, Eleanor; Lee-Thorp, Julia; Louys, Julien; Zalmout, Iyad; Al-Mufarreh, Yahya; et al.
Abstract Despite its largely hyper-arid and inhospitable climate today, the Arabian Peninsula is emerging as an important area for investigating Pleistocene hominin dispersals. Recently, a member of our own species was found in northern Arabia dating to ca. 90 ka, while stone tools and fossil finds have hinted at an earlier, middle Pleistocene, hominin presence. However, there remain few direct insights into Pleistocene environments, and associated hominin adaptations, that accompanied the movement of populations into this region. Here, we apply stable carbon and oxygen isotope analysis to fossil mammal tooth enamel (n  = 21) from the middle Pleistocene locality of Ti's al Ghadah in Saudi Arabia associated with newly discovered stone tools and probable cutmarks. The results demonstrate productive grasslands in the interior of the Arabian Peninsula ca. 300–500 ka, as well as aridity levels similar to those found in open savannah settings in eastern Africa today. The association between this palaeoenvironmental information and the earliest traces for hominin activity in this part of the world lead us to argue that middle Pleistocene hominin dispersals into the interior of the Arabian Peninsula required no major novel adaptation. Stable carbon and oxygen isotope analysis of mammal teeth associated with stone tools and cut-marked bone dated to between 300, 000 and 500, 000 years ago reveals that, at the time of the earliest-known hominin presence, the Arabian peninsula was home to productive grasslands similar to modern-day African savannahs.